Improvement and extension of ETRS 89 in Latvia and Lithuania based on the NKG 2003 GPS campaign - Jivall, Lotti; Kaminskis, Jānis; Paršeliūnas, Eimuntas (Geodesy and Cartography, 2012)
The present ETRS 89 realisations in Latvia and Lithuania are based on the EUREF‐BAL’92 campaign, which has an estimated accuracy of the same level as the original EUREF 89 campaign (class C). Latvia and Lithuania wish to replace their EUREF‐BAL’92 realisation with an ETRS 89 realisation based on the NKG 2003 GPS campaign. The NKG 2003 GPS campaign was carried out in GPS‐week 1238 (Sept 28th to Oct 4th 2003) under the framework of the Nordic Geodetic Commission (NKG). The campaign included mainly permanent stations in the Nordic and Baltic area as well as Island, Greenland and Svalbard. In Latvia, Lithuania and Denmark also field sites defining ETRS 89 were included. New ETRS 89 coordinates based on the NKG 2003 campaign have been calculated. The campaign resulted in a set of coordinates in ITRF 2000 epoch 2003.75. All stations in Latvia and Lithuania as well as a sub‐set of stations in neighbouring countries were converted to ETRS 89 using the standard procedure described by Boucher and Altamimi. No intraplate deformations have been taken into account, thus the epoch of the ETRS 89 coordinates is 2003.75. Estimated accuracy: 0,5–1 cm (95%) for the horizontal co‐ordinates and 1–2 cm (95%) for the vertical at the epoch of the observation. The computed ETRS 89 coordinates presented in this paper are to be considered as improvement and extension of ETRS 89 in Latvia and Lithuania based on the NKG 2003 GPS campaign. During symposia in Riga, 14–17 June 2006, the IAG Reference Frame Sub‐commission for Europe (EUREF) recognising, that in Sept‐Oct 2003 the EUREF‐NKG‐2003 campaign in Scandinavia and the Baltic countries was observed, including points in Latvia and Lithuania, and that the results of it were submitted to the EUREF Technical Working Group, where they were accepted as Class B standard (about 1 cm at the epoch of observation), endorses the subset of points submitted to the EUREF Technical Working Group as extension to the current realisation of ETRS89 (Resolution No 1). First published online: 03 Aug 2012